Relationship between Phenotypic and Genotypic Resistance of Subgingival Biofilm Samples in Patients with Periodontitis - Moritz Sparbrod; Yann Gager; Anne-Katrin Koehler; Holger Jentsch; Catalina-Suzana Stingu (Antibiotics, 2022)
The phenotypic expression of antibiotic resistance genes (ARGs) can hamper the use of antibiotics as adjuncts to subgingival instrumentation in the treatment of periodontitis patients. The aim of the study was to analyze the relationship between the phenotypic and genotypic resistance against ampicillin-sulbactam, clindamycin, doxycycline and metronidazole of subgingival biofilm samples from 19 periodontitis patients. Samples were analyzed with shotgun sequencing and cultivated anaerobically for 7 days on microbiological culture media incorporating antibiotics. All growing isolates were identified to the species level using MALDI-TOF-MS and sequence analysis of the 16S ribosomal RNA (rRNA) gene. Phenotypic resistance was determined using EUCAST-breakpoints. The genetic profile of eight patients matched completely with phenotypical resistance to the tested antibiotics. The positive predictive values varied from 1.00 for clindamycin to 0.57 for doxycycline and 0.25 for ampicillin-sulbactam. No sample contained the nimI gene. It can be concluded that antibiotic resistance may be polygenetic and genes may be silent. Every biofilm sample harboring erm genes was phenotypic resistant. The absence of cfx and tet genes correlated to 100%, respectively, to 75%, with the absence of phenotypic resistance. The absence of nimI genes leads to the assumption that constitutive resistance among several species could explain the resistance to metronidazole.